Pitting mechanism of mild steel in marginally sour environments – Part II: Pit initiation based on the oxidation of the chemisorbed iron sulfide layers. (15th May 2021) - Zhang, Wei; Brown, Bruce; Young, David; Singer, Marc
Highlights: Oxygen ingress was found as the reason why pitting occurred on mild steel in marginally sour environments. Only H2 S chemisorption layer was formed on steel surface before the saturation degree of mackinawite reached unity in the solution. This Sads (Fe) layer could protect steel surface from severe corrosion brought by H2 CO3 solution. However, Sads (Fe) layer could be partially compromised when [O2 ]aq > 3 ppb(w), leading to pitting initiation on mild steel in marginally sour environments. Abstract: The role of trace concentrations of O2 ( ca. 20 ppb(w) ) relating to pitting in marginally sour environments was investigated in this work. Laboratory experiments were conducted with X65 mild steel specimens at pH 5.00 ± 0.01, 30 °C, 0.97 bar CO2 and 0.04 mbar H2 S with/without O2 for up to 7 days. Acquired corrosion rate, the composition of the corrosion product layer, and surface profile after the layer was removed were compared. As a result, only H2 S chemisorption layer was formed without oxygen; this layer could be partially compromised when [O2 ]aq > 3 ppb(w), leading to pitting initiation.